The Hijriyah Calendar Perspective Islamic Law: What and How? - Misbah Khusurur; Istikharoh Istikharoh; Muhammad Anis Afiqi; Muhajir Muhajir; Mickael Jordan Wirayudha (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
In various countries with a Muslim majority population, the use of the Hijri calendar in Islamic law has significant implications. This calendar affects legal practices such as the determination of the start of Ramadan, family law, prayer times, and religious celebrations. However, there are differing opinions and challenges in harmonizing Islamic legal provisions based on the Hijri calendar with national positive law. The purpose of this research is to identify the significance of using the Hijri calendar in the context of Islamic law and to understand how its use adapts to changes in time and globalization. The research method used is normative legal research with a legislative approach and the analysis of legal documents and legal literature to identify the use of the Hijri calendar in Islamic law. The data analysis technique used is a qualitative approach to answer research questions about the contribution of the Hijri calendar to Islamic law and its adaptation to changes in time and globalization. The results of the research show that the use of the Hijri calendar in Islamic law has significant impacts, including the determination of the start of Ramadan, influence on inheritance law, determination of prayer times, and commercial transactions. Furthermore, the Hijri calendar reflects the religious and cultural values in Muslim society, although there are challenges regarding the recognition of Islamic law in different legal contexts. This research highlights the importance of a thorough understanding of the use of the Hijri calendar in Islamic law. Additionally, the adaptation of the Hijri calendar to changes in time and globalization involves changes in determining the start of Ramadan, its use in civil law, adjustment to time zones, its role in international agreements, and dealing with conflicts with the Gregorian calendar